Delving into international students’ attitudes to NESTs and NNESTs - Sureepong Phothongsunan, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study examined the attitudes of international students at university level towards native English-speaking teachers (NESTs) and non-native English speaking teachers (NNESTs) in a Thai context. It also explored how the attitudes held towards these two groups of teachers shaped the participants’ learning practices and motivation to learn English. Two research instruments; the open-ended questionnaire and the semi-structured interview were employed for this study. The questionnaire administered with 31 participants was the primary data collection tool. The subsequent interview conducted with 14 of the participants served as a supplementary data. The findings indicated significantly differing attitudes towards native English-speaking teachers and nonnative English speaking teachers in many areas. These domains comprised the teaching methods and styles; the understanding of students’ problems; grading and marking; language proficiency; personality, classroom behaviour and discipline; and the ability to communicate and interact with learners. Some differences were also reported in the way they assigned work and arranged learning activities and their attitudes towards students. Most participants given the choice had a strong favour to study with native English-speaking teachers. There appeared to be a strong positive rapport between studying with native English speaking teachers and the participants’ learning behaviours and eagerness to study English. Implications are made regarding teacher training, particularly for non-native English teachers and language teachers, be it native or non-native, having EFL teaching experience.